1975
DOI: 10.1007/bf00126992
|View full text |Cite
|
Sign up to set email alerts
|

Pure bending of helically wound ideal fibre-reinforced cylinders

Abstract: An ideal fibre-reinforced material is defined to be inextensible in one or more directions through each point of the material. It has been found to be a good model for predicting the deformation and stresses produced in real materials which are very much stronger in resisting extension in those directions than in any other possible mode of deformation.We consider a circular cylindrical tube of incompressible ideal fibre-reinforced material in which the reinforcement throughout its thickness is directed along t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1977
1977
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…This value is surprisingly similar to the adventitial fibre angle measured in experiments ( Holzapfel et al, 2000 ; Schriefl et al, 2012 ). However, this should be viewed with caution since the presence of fibres is not exactly equivalent to the inextensible case of Spencer et al (1975) , and hence the agreement on the value of β A could be a coincidence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This value is surprisingly similar to the adventitial fibre angle measured in experiments ( Holzapfel et al, 2000 ; Schriefl et al, 2012 ). However, this should be viewed with caution since the presence of fibres is not exactly equivalent to the inextensible case of Spencer et al (1975) , and hence the agreement on the value of β A could be a coincidence.…”
Section: Discussionmentioning
confidence: 99%
“…At this point, it is worth noting that Spencer et al (1975) considered a circular cylindrical tube of incompressible ideal fibre-reinforced material in which the reinforcement throughout its thickness is directed along two families of helices making angles of ± β A . Of particular importance, they argued that , so that β A = 54.7° in order to avoid the narrow bands of stress concentration near the surfaces at the inner and outer radii.…”
Section: Discussionmentioning
confidence: 99%
“…The magic angle is the optimal winding angle for the design of filament-wound structures and, as mentioned earlier, is often derived in the composite structures literature by netting analysis (see, for example, [18]). An application of the idealized linear theory to bending of helically wound tubes is carried out in Spencer et al [12], where again it is shown that reinforcement at the magic angle (1.3) leads to considerable simplification. A review of such results and extensions to large elastic and plastic deformations is given by Rogers [19].…”
Section: While the Condition Of Inextensibility Ismentioning
confidence: 99%
“…The first papers in which the magic angle occurs in the linear idealized theory appear to be those of Spencer et al [11,12]. In these papers, the problem of a circular cylindrical tube reinforced by a double family of helically wound fibres is considered.…”
Section: While the Condition Of Inextensibility Ismentioning
confidence: 99%
See 1 more Smart Citation